TECHNOLOGY IN MATHEMATICS: STUDENTS PERSPECTIVE - Mohd Sulhi bin Azman (Proceedings of ICMSA, 2005)
Technology is one of the current advances utilized in the learning andteaching of Mathematics. Recently, technology plays a vital role invarious fields and aspects - particularly in mathematics. Technology isan advance paradigm of human civilization since it is one of the newinventions required in the modem world. We view that technology is acatalyst for critical thinking, a vehicle for integralion and a tool forexpediancy. In recent years, mathematics educator employedtechnology and use it as part of teaching aids. The pedagogical notionof "pencil-paper" method has now been replaced by advancetechnological tool such as graphics calculator (GC). This suggests thattechnolory enhance students' performance in Mathematics. This paperexamines the role and use of technology in enhancing students'performance in Mathematics. Various examples including computeralgebra system (CAS) and graphic calculator (GC) are discussed inorder to support the idea of integration of technology in mathematics.In this paper, we will also identify the benefit of these current advances(i.e. technology) from many perspectives. Inter-dependent andcollaborative leaming are achieved by integrating conceptualmathematics with technology.